99 poems new & selected - Gioia, Dana 1950- (Graywolf Press, 2016)
99 Poems: New & Selected for the first time gathers work from across his career, including a dozen remarkable new poems. Gioia has not ordered this selection chronologically. Instead, his great subjects organize this volume into broad themes of mystery, remembrance, imagination, place, stories, songs, and love. The result is a book we might live our lives alongside, and a reminder of the deep and abiding pleasures and reassurances that poetry provides us
Includes index